2015
DOI: 10.1017/s002237781500080x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of zonal flow and magnetic field in the ionospheric E-layer

Abstract: We review the generation of zonal flow and magnetic field by coupled electromagnetic ultra-low-frequency waves in the Earth’s ionospheric E-layer. It is shown that, under typical ionospheric E-layer conditions, different planetary low-frequency waves can couple with each other. Propagation of coupled internal-gravity–Alfvén, coupled Rossby–Khantadze and coupled Rossby–Alfvén–Khantadze waves is revealed and studied. A set of appropriate equations describing the nonlinear interaction of such waves with sheared z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Nonlinear dynamics of CRAK EM planetary modes in the ionospheric E-layer is investigated (see details in [16] [30]). It is shown that under the prevalent action of Hall conductivity, owing to the latitudinal non-homogeneity of both the Coriolis parameter and stationary geomagnetic field, a new type of CRAK wave can propagate.…”
Section: Generation By Crak Wavesmentioning
confidence: 99%
See 3 more Smart Citations
“…Nonlinear dynamics of CRAK EM planetary modes in the ionospheric E-layer is investigated (see details in [16] [30]). It is shown that under the prevalent action of Hall conductivity, owing to the latitudinal non-homogeneity of both the Coriolis parameter and stationary geomagnetic field, a new type of CRAK wave can propagate.…”
Section: Generation By Crak Wavesmentioning
confidence: 99%
“…But during the last decade a great amount of publications revealed different nonlinear mechanisms leading to the generation of sheared zonal flow. Namely the excitation of zonal flow based on the triple planetary waves nonlinear parametric instability in the Earth's ionospheric medium was widely investigated (see [14] [16]- [30] and references cited in).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jian et al (2009) investigated non-linear propagation of Rossby waves in stratified neutral fluids with zonal shear flow and obtained a modified Korteweg-de Vries (mKdV) equation with cubic non-linearity. Generation of the zonal flow along with the magnetic field in the ionospheric E plasma by Rossby-Khantadze EM planetary waves was also discussed (Kaladze et al, 2012;Kahlon and Kaladze, 2015). The possibility of a magnetic field generation of 10 3 nT is predicted.…”
Section: Introductionmentioning
confidence: 98%